Legal Protection of Sami Traditional Livelihoods from the Adverse Impacts of Mining: A Comparison of the Level of Protection Enjoyed by Sami in Their Four Home States - Timo Koivurova; Vladimir Masloboev; Kamrul Hossain; Vigdis Nygaard; Anna Petrétei; Svetlana Vinogradova (Arctic Review on Law and Politics, 2015)
As a consequence of the growing global need for minerals, extractive industries are continuously expanding. In the North, together with several environmental problems such as climate change, this poses a real threat to the traditional livelihoods of Sami people. The article examines how the rights of Sami indigenous people are protected against adverse impacts of mining activities. The relevant national legislation is analyzed in all the four countries where Sami are present. It is specifically examined how the main mining act in each country protects the right of Sami people to their traditional livelihoods. Finally, the article sheds light on the actual effectiveness of the legal regulation. This is done by analyzing the results of interviews conducted with relevant actors and stakeholders in the mining industry.